Α-Hydroxyphosphonic acid derivatives of 2-azanorbornane: synthesis, DFT calculations, and crystal structure analysis. Issue 12 (15th July 2015) - Olszewski, Tomasz K.; Wojaczyńska, Elżbieta; Wieczorek, Robert; Bąkowicz, Julia
Graphical abstract: Abstract: Highly diastereoselective hydrophosphonylation of 2-azanorbornane aldehyde exo -1 with silylated phosphorus esters yielded the ( S )-α-hydroxyphosphonic acid exo -3a . The use of endo -2 gives the isomer with the opposite configuration at the new stereogenic center ( R )- endo -4a . X-ray analysis revealed that exo -3a crystallizes in the orthorhombic space group P 21 21 21 with two crystallographically independent molecules, one zwitterionic and the other forming a salt with HBr. Abstract : endo -(( R )-Hydroxy((1 S, 3 S, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl)methyl)phosphonic acid: C15 H22 NO4 P [ α ]D 20  = +30.0 ( c 1.0, H2 O) Source of chirality: endo -(1 S, 3 S, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptane Absolute configuration: (1 S, 3 S, 4 R, 1′ S, 1″ R ) Abstract : exo -(( R )-Hydroxy((1 R, 3 S, 4 S )-2-(( R )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl)methyl)phosphonic acid: C15 H22 NO4 P [ α ]D 20  = −18.8 ( c 1.0, H2 O) Source of chirality: exo -(1 R, 3 S, 4 S )-2-(( R )-1-phenylethyl)-2-azabicyclo[2.2.1]heptane Absolute configuration: (1 R, 3 S, 4 S, 1′ R, 1″ R ) Abstract : exo -(( S )-Hydroxy((1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl)methyl)phosphonic acid: C15 H22 NO4 P [ α ]D 20  = −19.0 ( c 0.8, H2 O) Source of chirality: exo -(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptane Absolute configuration: (1 S, 3 R, 4 R, 1′ S, 1″ S )